Enhanced infectivity of strains of Helicobacter pylori isolated from children compared with parental strains. Issue 4 (26th February 2019) - Zaman, Cynthia; Osaki, Takako; Furuta, Yoshikazu; Hojo, Fuhito; Yonezawa, Hideo; Konno, Mutsuko; Kurata, Satoshi; Hanawa, Tomoko; Kamiya, Shigeru
Abstract : Purpose. Intra-familial infection, mother-to-child infection, is considered to be one of the main routes of transmission for Helicobacter pylori, in developed countries such as Japan. A major role for intra-familial spread in the pathogenicity of H. pylori is now beyond controversy, although the major route of transmission remains poorly understood. We performed this study to clarify the factors determining intra-familial transmission. Methodology. We used several H. pylori strains isolated from family members to compare infectivity. H. pylori K21 and K22 strains were isolated from the father and mother, and the K25 strain was isolated from the third child of the family. Mongolian gerbils were inoculated with H. pylori strains and the infectivity of three strains was compared in each experiment. In addition, the whole genome sequence, adhesion to gastric epithelial cells and the growth of static condition or continuous flow culture among three strains of H. pylori were analysed. Results/Key findings. Most of the colonies were determined as the same molecular type K25 in all of the four grouped animals and H. pylori K25 was observed as the dominant strain. The stronger adhesion capacity of the K25 strain was observed in comparison with the other two strains through in vitro analysis. By assessing the genomic profiles of H. pylori isolates from three strains, identified TnPZ regions were detected only in the K25 strain. Conclusion. The infectivity of H. pylori isolates intra-familial infection and animal infection were prescribed by the adhesion capacity and molecular type of each strain.